Pathological and molecular insights into intravenous leiomyomatosis: an integrative multi-omics study - Sheng Yin; Peipei Shi; Jing Han; Hua Li; Aimin Ren; Li Ma; Wenbin Tang; Wenxue Liu; Sihui Yu; Tingting Li; Chunsheng Wang; Yingyong Hou; et al. (Journal of Translational Medicine)
Abstract Intravenous leiomyomatosis (IVL) is a histologically well differentiated smooth muscle tumor with aggressive behavior, capable of extending throughout the venous system. Understanding how IVL occurs and develops is really important for diagnosing and treating it. Unfortunately, because IVL is quite rare, there aren’t many comprehensive studies available. In our research, we carried out an extensive multi-omics study, gathering tissue samples from IVL cases, uterine fibroid, and normal myometrium. The single-cell RNA sequencing analysis revealed a notable difference in cell composition between IVL and uterine fibroid. Additionally, H&E staining demonstrated more frequent hydropic changes and hyalinization in IVL tissues, along with a reduced vascular density compared to both normal myometrium and uterine fibroid. In our proteomics analysis of eight paired samples of IVL and normal myometrium fresh frozen tissue, we identified proteins that were differentially expressed, mainly related to focal adhesions and regulation of the actin cytoskeleton. The most frequently involved chromosomes included deletions in 10q22.2, 10q24.32, 13q14, and 13q21-31. Correlation analyses highlighted chromosome 10q as the most frequent cytoband, with corresponding proteins involved in regulating focal adhesions and the cytoskeleton. Integrated analysis between pathological and clinical characteristics indicated that chromosome 10q deletion and vascular morphology in IVL could serve as important markers predicting aggressive behavior. Our study sheds light on the pathological and molecular changes linked to IVL, which could pave the way for new treatment approaches.